Endoscopic early detection of premalignant changes in stomach with mucosal biopsy in patients with symptomatology of acid peptic disease - Gujar, Ajay A.; Gujar, Geeta A. (International Journal of Research in Medical Sciences, 2016)
Background: Stomach cancer is the second-most common cancer among men and third-most among females in Asia and worldwide. The symptoms and sign of the stomach cancer are often reported late when the disease is already in advanced stages and 5-year survival is less than 30% in developed countries and around 20% in developing countries. Early detection of cancer stomach is still remains challenge to the gastroenterologist. Methods: This study was done to detect early premalignant changes by upper GI scopy and histopathological examinations of mucosal biopsies in patients with symptoms of acid peptic disease not responding to any type of medications. 200 patients above 20 years of age with acid peptic disease symptoms selected for upper GI scopy and histopathology with follow up from 6 months to two years to detect whether premalignant lesion changes to malignancy. Results: Different types of inflammatory lesions of gastric mucosa detected endoscopically and on histopathology in our study. In 7 patients premalignant changes were detected and 7 patients already had gross malignancies in stomach. Out of the total number of biopsies included in the study, we observed lesions of atrophic type in 4 antral biopsies (2.25%) and 3 biopsies of the gastric body (1.69%). All were grade 1 as per Sydney classification. Conclusions: Upper endoscopy with histopathology has excellent output to detect early premalignant changes in stomach mucosa, though it is long way to continue this study to correlate both.